The Influence of Hard Skills, Future Time Perspective, and Internship Experience on Job Readiness : The Influence of Hard Skills, Future Time Perspective, and Internship Experience on Job Readiness - Emawati, Nia Putri; Violinda, Qristin; Dharmaputra, M Fadjar (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to determine the influence of hard skills, future time perspective, and internship experience on the work readiness of PGRI University Semarang students. This type of research is quantitative, the research population is students from the 2018, 2019 and 2020 classes who have entered their final semester, totaling 7,300 students. This research uses probability sampling techniques with a sample size of 618 students. The measurements in this research used a Likert scale which was then processed with the IBM SPSS Statistics Version 26 analysis tool using multiple linear regression analysis. The results of this research show that there is an influence between hard skills on work readiness, there is an influence of future time perspective on work readiness, there is an influence of internship experience on work readiness. It can be seen in the Summary table with an Adjusted R Square value of 0.443 X 100% = 44.3%.